Targeted therapies with companion diagnostics in the management of breast cancer: current perspectives - Myers MB (Dove Medical Press, 2016)
Meagan B Myers Division of Genetic and Molecular Toxicology, National Center for Toxicological Research, US Food and Drug Administration, Jefferson, AR, USA Abstract: Breast cancer is a multifaceted disease exhibiting both intertumoral and intratumoral heterogeneity as well as variable disease course. Over 2 decades of research has advanced the understanding of the molecular substructure of breast cancer, directing the development of new therapeutic strategies against these actionable targets. In vitro diagnostics, and specifically companion diagnostics, have been integral in the successful development and implementation of these targeted therapies, such as those directed against the human epidermal growth factor receptor 2. Lately, there has been a surge in the development, commercialization, and marketing of diagnostic assays to assist in breast cancer patient care. More recently, multigene signature assays, such as Oncotype DX, MammaPrint, and Prosigna, have been integrated in the clinical setting in order to tailor decisions on adjuvant endocrine and chemotherapy treatment. This review provides an overview of the current state of breast cancer management and the use of companion diagnostics to direct personalized approaches in the treatment of breast cancer. Keywords: HER2, precision medicine, in vitro diagnostics, estrogen receptor, multigene assay